THE ROLE OF JOB SATISFACTION IN MEDIATING THE INFLUENCE OF WORK-LIFE BALANCE AND EMOTIONAL INTELLIGENCE ON CIVIL SERVANT PERFORMANCE - Nov Fitri; Syahran Syahran (Universitas KH. Abdul Chalim Mojokerto, 2026)
Changes in work patterns and increasing demands for public services require civil servants to maintain optimal and sustainable performance. This study aims to analyze the influence of work-life balance and emotional intelligence on civil servant performance, with job satisfaction as a mediating variable. The study used an explanatory quantitative approach with a survey method of 384 ASN in the Tana Tidung Regency Government. Data were collected through structured questionnaires and analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). The results showed that emotional intelligence had a positive and significant effect on job satisfaction and ASN performance. Job satisfaction also has a significant effect on performance. Meanwhile, work-life balance has a significant effect on job satisfaction, but does not have a direct effect on performance. Indirect effect analysis proves that job satisfaction acts as a significant mediating variable in the relationship between emotional intelligence and performance, as well as between work-life balance and civil servant performance. These findings emphasize the importance of psychological factors in improving civil servant performance and provide implications for the development of human resource management policies oriented towards work-life balance and job satisfaction.